Die ungleichen Brüder : zum Verhältnis zwischen schwulen und heterosexuellen Männern - Kraushaar, Elmar; Grimme, Matthias T.J. (Reinbek bei Hamburg : Rowohlt, 1988)
Fonds Suzan Daniel (FSD)
Duits
Monografie